Analisis Faktor-Faktor yang Mempengaruhi Intensitas Bermain Game Roblox pada Remaja - Adinda Fajarwati; Gita Rahmania; Karinna Putri; Nabil Abdurrahman; Tiffany Dwi Ardana; Yofa Putri Adinda (Indonesian Journal Publisher, 2026)
This study examines psychological and social factors influencing adolescents’ gaming behavior on Roblox. A qualitative descriptive approach with thematic analysis was applied. Data were collected from 150 participants aged 13–21 through open-ended questionnaires. The findings reveal that gaming motivation is influenced by entertainment needs, boredom, fear of missing out (FOMO), peer influence, and game features. High gaming intensity (more than 3 hours per day) indicates a tendency toward addictive behavior, particularly when gaming functions as a coping mechanism. Roblox provides positive impacts such as enhanced creativity and social interaction, but also negative consequences including sleep disruption, reduced productivity, and decreased offline engagement. The findings highlight that excessive gaming behavior results from the interaction of emotional, social, and game-design factors.